SISTEM PAKAR DIAGNOSIS PENYAKIT TANAMAN SEMANGKA DENGAN MENGGUNAKAN METODE ANALYTICAL HIERACHY PROCESS DAN CERTAINTY FACTOR - fadilah, syindy nur; Gunawan, Harry; Iskandar, Iskandar (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2024)
Diseases in watermelon plants can cause significant losses for farmers. A lack of information about these diseases risks worsening the condition of the plants. To address this issue, the development of an expert system for diagnosing watermelon diseases offers an effective solution. This system uses the Analytical Hierarchy Process (AHP) method to assign weights to symptoms based on pairwise comparisons and Certainty Factor to determine the level of confidence in the diagnosis. As a web-based system, it ensures easy access and allows farmers to diagnose diseases quickly and accurately. With this system, farmers can more efficiently manage diseases in watermelon plants, reducing the negative impact on crop yields and helping to maintain the sustainability of agricultural operations. Keywords: Expert System, Diagnosis, Watermelon Plant Disease, Analytical Hierarchy Process (AHP), and Certainty Factor